Alternative forms of dispute resolution - Ali Mohamed, Ashgar Ali (Malaysian Current Law Journal, 2014)
Litigating disputes in the ordinary courts of law is costly, time-consuming with unpredictable outcome and above all, the ‘winner takes all’ and this, inevitably, would damage irreparably the relationships between the disputants. In the administration of justice, the courts are often busy with an accumulated backlog of cases. The undue delay affects the disputants tremendously in terms of reputation, time and costs. There has been dissatisfaction expressed by the public for the inordinate and inexcusable delay in the disposal of cases in the courts in Malaysian and often blame has been leveled against the courts, when in fact there are other factors that have equally contributed to the delay. Lengthy and convoluted court procedures have been identified as the main reason for the delay in the disposal of cases in the courts. These are apart from the shortage of manpower in courts and unnecessary requests for adjournment among others. Hence, this chapter highlights firstly the constrains of the traditional mode of dispute settlement, and thereafter discusses the alternative modes of dispute resolutions with special reference to mediation and arbitration.